Exposure to an extremely low-frequency electromagnetic field only slightly modifies the proteome of Chromobacterium violaceum ATCC 12472 - Rafael A. Baraúna; Agenor V. Santos; Diego A. Graças; Daniel M. Santos; Rubens Ghilardi Júnior; Adriano M. C. Pimenta; Marta S. P. Carepo; Maria P.C. Schneider; Artur Silva (Genetics and Molecular Biology, 2015)
Several studies of the physiological responses of different organisms exposed to extremely low-frequency electromagnetic fields (ELF-EMF) have been described. In this work, we report the minimal effects of in situ exposure to ELF-EMF on the global protein expression of Chromobacterium violaceum using a gel-based proteomic approach. The protein expression profile was only slightly altered, with five differentially expressed proteins detected in the exposed cultures; two of these proteins (DNA-binding stress protein, Dps, and alcohol dehydrogenase) were identified by MS/MS. The enhanced expression of Dps possibly helped to prevent physical damage to DNA. Although small, the changes in protein expression observed here were probably beneficial in helping the bacteria to adapt to the stress generated by the electromagnetic field.